Impact of temperament and autistic traits on psychopathology in Japanese children: A nationwide cross-sectional study. (1st April 2018) - Kamio, Yoko; Takei, Reiko; Stickley, Andrew; Saito, Aya; Nakagawa, Atsuko
Abstract: Although temperament has been linked to psychopathological outcomes in non-clinical children, little is known about the association between temperament and psychopathological outcomes in children on the autism spectrum whose psychopathological outcomes are highly variable. The current study examined the impact of temperament and autistic traits on emotional and conduct problems during school age in a large-scale sample of non-clinical children with the use of quantitative scales. Cross-sectional data comprising parent reports of recalled temperament, current emotional and conduct problems, and current autistic traits for Japanese children aged 6–15 years ( N  = 24, 232) that were collected with a postal questionnaire were analyzed. The results showed that emotional and conduct problems in school age were associated with both autistic traits and toddlerhood temperament. Specific temperament-psychopathology associations between higher negative affectivity and more emotional problems, higher effortful control and fewer conduct problems, and higher surgency and more conduct problems were shared among children with different levels of autistic traits. This study showed that although temperament in toddlerhood differed by the degree of autistic traits, both temperament and autistic traits could predict emotional and conduct problems in school-age children, and that the temperament-psychopathology associations are in most respects universal regardless of the degree of autistic traits. Highlights: Temperament in toddlerhood differs by the degree of autistic traits. Both toddlerhood temperament and autistic traits predict childhood psychopathology. Temperament-psychopathology relation is universal regardless of autistic traits.